2022
DOI: 10.1186/s12933-022-01706-2
|View full text |Cite
|
Sign up to set email alerts
|

Body mass index versus surrogate measures of central adiposity as independent predictors of mortality in type 2 diabetes

Abstract: Background An “obesity paradox” for mortality has been shown in chronic disorders such as diabetes, and attributed to methodological bias, including the use of body mass index (BMI) for obesity definition. This analysis investigated the independent association of BMI versus surrogate measures of central adiposity with all-cause mortality in individuals with type 2 diabetes. Methods The Renal Insufficiency And Cardiovascular Events Italian Multicent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 51 publications
(79 reference statements)
1
5
0
Order By: Relevance
“…In line with our observations, previous studies involving primarily white ethnic populations have consistently reported a positive relationship between ABSI and all-cause mortality in people with diabetes [ 6 , 14 , 29 ]. In the Fremantle Diabetes Study of Australian patients with type 2 diabetes, people in the fifth ABSI quintile had an elevated risk of all-cause mortality compared with those in the first quintile [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In line with our observations, previous studies involving primarily white ethnic populations have consistently reported a positive relationship between ABSI and all-cause mortality in people with diabetes [ 6 , 14 , 29 ]. In the Fremantle Diabetes Study of Australian patients with type 2 diabetes, people in the fifth ABSI quintile had an elevated risk of all-cause mortality compared with those in the first quintile [ 6 ].…”
Section: Discussionsupporting
confidence: 92%
“…ABSI is the obesity indicator most strongly associated with all-cause mortality when compared with BMI, waist circumference, and WHR in their analysis [ 6 ]. Similarly, in a prospective cohort study on Italian Caucasians, the highest risk was found in the third ABSI tertile group [ 14 ]. However, none of these studies have reported data on cardiovascular mortality.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations